'[A]n inn to entertain / Its Lord a while, but not remain': Home and Dislocations in Andrew Marvell's 'Upon Appleton House'. - Markidou, Vassiliki (Critical Survey, 2010)
This essay analyses Andrew Marvell's 'Upon Appleton House' and demonstrates that the poem registers the ways in which spatial politics, and the representation of home, in particular, underpins as well as enriches its meaning. Borrowing Donna Birdwell-Pheasant's and Denise Lawrence-Zuniga's definition of home and house the essay focuses on Lord Fairfax's house and shows that, notwithstanding the multiplicity of spaces presented in the particular poem, and despite his agonising effort to present Nunappleton as Lord Fairfax's home, Marvell in fact reflects his patron experiencing a strong sense of dislocation while living in Appleton House due to its complex as well as disconcerting religious and familial associations. In other words, beneath the façade of the heroic Protestant man who chose to withdraw from the public arena to the private sphere of Nunappleton, was a man trying to come to terms with his Catholic origins as well as with the fact that the particular estate reminded him of his displacement from the male line of his family as well as his disempowerment by the female sex. Hence, Appleton House, at that precise historical moment, fails to become 'a symbol of self' or 'a manifestation of family identity'; instead it is 'an inn to entertain / Its Lord a while, but not remain' (ll. 71-72).